Հուշագրության ժանրի գեղարվեստական հայեցակերպը ժամանակի կարգի քննության լույսի ներքո - Էվելինա Զադոյան (ՀՀ ԳԱԱ հրատ.)
Данная статья относится к поджанру мемуарного автобиографического жанра. В данной исследовательской работе рассматриваются особенности художественного мемуара в тесной связи с категорией времени, а также соотношение мемуара как факт-текст с художественным текстом и роль автора в создании этого жанра.This article considers the distinctive features of the autobiographical genre in memoirs. These features are studied in close relation with the time factor. The connection of memoirs with actual facts and fictional ones as well as the role of the author in creating this genre are also considered.
Keywords: Language and Literature